Comparative study on isolation and mitochondrial function of adult mouse and rat cardiomyocytes. (November 2019) - Liu, Bilin; Li, Anqi; Qin, Yuan; Tian, Xiangang; Gao, Meng; Jiang, Wenting; Gong, Guohua
Abstract: Background: Cultured adult mouse and rat cardiomyocytes are the best and low-cost cell model for cardiac cellular physiology, pathology, drug toxicity screening, and intervention. The functions of mouse cardiomyocytes decline faster than rat cardiomyocytes in culture conditions. However, little is known about the difference of mitochondrial function between cultured mouse and rat myocytes. Methods and results: A large number of adult mouse and rat cardiomyocytes were comparative isolated using a simple perfusion system. Cardiomyocytes mitochondrial functions were measured after 2 h, 1 day, 2 days, 3 days, and 4 days culture by monitoring mitoflashes. We found that the mitochondrial function of mouse myocytes was remarkedly declined on the third day. Then, we focused on the third day cultured mouse and rat myocytes, comparatively analyzing the respiration function and superoxide generation stimulated by pyruvate/malate/ADP and the mitochondrial permeability transition pore (mPTP) opening induction. Mouse myocytes showed lower respiration and mitoflash activity, but without the change of maximum uncoupled respiration when compared with rat myocytes. Although the response to superoxide production stimulated by respiration substrates was slower than rat myocytes, the basal superoxide generation is faster than the rat. The faster mitochondrial reactive oxygen species (ROS) generation of mouse myocytes upon laser stimulation triggered the faster mPTP opening compared with the rat. Finally, antioxidant MitoTEMPO pretreatment preserved the mitochondrial function of mouse myocytes on the third day. Conclusions: The mitochondrial function and stability are different between cultured mouse and rat cardiac myocytes beyond 3 days even though they both belong to Muridae. Mitochondrial ROS impairs the mitochondrial functions of mouse cardiomyocytes on the third day. Suppressing superoxide maintained the mitochondrial function of mouse myocytes on the third day. Highlights: High-quality isolation of cardiomyocytes from adult mice and rats is different. Mitochondrial function of cultured adult mouse and rat myocytes is steady in 2 days. Rat myocyte's mitochondria are more stable than the mouse during long-term culture. Mitochondrial ROS leads to the functional decline of cultured mouse cardiomyocytes.